2019
DOI: 10.1007/s11250-019-02072-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Treponema species organisms in foremilk and udder cleft skin of dairy cows with digital dermatitis

Abstract: Identification of reservoirs and transmission routes of digital dermatitis (DD) associated Treponema spp. considered an effective means for controlling DD infection in dairy cows. The objective of this study is to identify and characterize the potential reservoir niches for DD-associated Treponema spp. from healthy udder cleft skin and foremilk in lactating dairy cows. A large dairy farm was visited weekly from March to July 2015. Clinical investigation revealed that a total of 25 lame cows had DD lesions loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…Treponemes were not found via histopathology, including in the Wharthin-Starry stain. The absence of these potential causes is in contrast with the findings of some other studies (Warnick et al, 2002;Stamm et al, 2009;Sobhy et al, 2019). Our findings are in line with the study of Sorge et al (2019), in which also no involvement of treponemes or mites could be demonstrated.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Treponemes were not found via histopathology, including in the Wharthin-Starry stain. The absence of these potential causes is in contrast with the findings of some other studies (Warnick et al, 2002;Stamm et al, 2009;Sobhy et al, 2019). Our findings are in line with the study of Sorge et al (2019), in which also no involvement of treponemes or mites could be demonstrated.…”
Section: Discussionsupporting
confidence: 85%
“…Warnick et al (2002) studied the possible involvement of Sarcoptes mites but concluded that parasitic control did not eliminate UCD lesions. Other studies suggest the involvement of treponemes, based on a positive correlation between the prevalence of UCD and digital dermatitis on farm level or detection of treponemes in udder skin or foremilk (Stamm et al, 2009;Evans et al, 2010;Sobhy et al, 2019). However, this was not supported by a recent study by Sorge et al (2019), in which the authors concluded that it seemed unlikely that spirochetes play a major role in the development of UCD.…”
Section: Introductionmentioning
confidence: 94%
“…Another study suggested that foremilk and udder cleft skin might be an important reservoir for Trepenoma spp. [81] (Table 1).…”
Section: Bovine Digital Dermatitismentioning
confidence: 99%
“…Another study suggested that foremilk and udder cleft skin might be an important reservoir for Trepenoma spp. [79].…”
Section: Bovine Digital Dermatitismentioning
confidence: 99%